2021
DOI: 10.1088/1757-899x/1076/1/012070
|View full text |Cite
|
Sign up to set email alerts
|

Gasoline Engine Simulation Software: A Comparison Review

Abstract: In this review, a survey of previous studies has been conducted on the use of simulation software to evaluate the performance of spark igniting engines. Some of the gaps in the simulation software used by researchers requiring further research and consideration of their potential impact on the writing of the topic under discussion. The results of the simulation software have led to the ability of these models to predict engine performance, and show good agreement between the experimental results and the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…On the other hand, because biodiesel has a lower calorific value than diesel fuel, the heat produced during the combustion process of biodieselfueled engines is less than that of diesel fuel-fueled engines. Biodiesel generated less heat and had a higher density than diesel fuel, which resulted in a lower value of BTE than diesel [118], [119]. There has been investigation on additives and the that they have on BTE.…”
Section: Brake Thermal Efficiency (Bte)mentioning
confidence: 99%
“…On the other hand, because biodiesel has a lower calorific value than diesel fuel, the heat produced during the combustion process of biodieselfueled engines is less than that of diesel fuel-fueled engines. Biodiesel generated less heat and had a higher density than diesel fuel, which resulted in a lower value of BTE than diesel [118], [119]. There has been investigation on additives and the that they have on BTE.…”
Section: Brake Thermal Efficiency (Bte)mentioning
confidence: 99%
“…The ability of the models created by simulation studies to predict the engine performance and emissions and hence to be compatible with experimental results shows the reliability of the studies. 32 Engine performance and emission characteristics have been determined in the case of using different mixtures of ethanol, methanol, butanol, and gasoline in an SI engine modeled with the Boost tool of AVL software. In these studies, it is observed that the output power has reduced, and brake-specific fuel consumption has increased when alcohol-based fuels have been used compared to gasoline mode.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the widespread interest in this technology, many nations, notably the United States, Australia, Greece, and Israel, have developed significant industries related to it [1]. While it's encouraging to see a rise in the use of solar water heaters in homes, it's important to highlight the sector's continued technical constraints [2]. The core design and operation of solar water heaters have changed very little over the previous two decades, despite the extraordinary advances in manufacturing and product quality.…”
Section: Introductionmentioning
confidence: 99%